Social and radical constructivism, teaching context, students' motivational beliefs, mathematics achievement and retention - Aggabao, Ambrose Hans G. (2006)
This study was conducted to have a better understanding of the influence of radical and social constructivist teaching approaches on motivational beliefs of students. A three-group pretest-posttest experimental design was used. Three groups of freshmen college students were exposed to radical constructivist approach, social constructivist approach, and the traditional teaching approach. The Motivational Belief Scale and Mathematics Achievement Test were also used in the study. Results showed that teaching approach has significant effects on motivational beliefs of students on all areas of achievement and retention. The radical and social constructivist teaching approaches emerged as significant predictors of most achievement and retention areas. Teachers' behavior, students' interaction, and instructional materials are also potential moderators of students' motivational beliefs.
"June 2006."
Thesis (Ph.D. Education : Mathematics Education)--University of the Philippines, Diliman.
Keywords: Constructivism (Education); Achievement motivation -- Philippines -- Isabela; Mathematical ability